Development of the educational App, Beesin My Garden, as an innovative tool forbees learning about bees - Hernández-Ching, Paola (2023)
Poster para presentar en el APIMONDIA : 48th Congreso Internacional de Apicultura ( 2023: setiembre 4-8 : Santiago, Chile)